'Communities of resistance' and the use of newspaper discussion boards: Polish workers in Japanese foreign investments. (July 2017) - Bancarzewski, Maciej; Hardy, Jane
Abstract : This article examines the content of 200 posts on newspaper discussion boards by workers in a cluster of Japanese foreign investments in Poland. The conclusions are first, that the material experiences of workers generate a set of themes in relation to the labour process with regard to wages and working conditions, bullying and monitoring that exhibit similarities across countries. Second, we argue that an analysis of the discourse used is shaped by political and institutional conditions, which reveal national differences in how workers perceive and locate their exploitation. Finally, in relation to debates about workers' resistance and the use of the Internet we argue that the interaction of themes related to the material experience of work are intertwined with institutionally embedded understandings of exploitation, which not only enable a shared framework for venting, but also provide the basis for a community of resistance.